79‐3: Video‐rate Holographic Display in ZnSe layer‐assisted Quantum Dot Doped Liquid Crystal with High‐photorefractive Sensitivity. Issue 1 (2nd June 2017) - Li, Xiao; Song, Zhicheng; Li, Fulin; Dong, Xiaobin; Liu, Weidong
Abstract : In this paper, we demonstrate a dynamic holographic display in ZnS/InP doped liquid crystal with assistance of ZnSe layer. The photorefractive effect of the hybrid cell is investigated. The response time of several to tens of milliseconds is measured with very low recording intensity (1 mW/cm 2 ) at 460 nm. The photosensitivity S of the hybrid LC cell is measured up to 2.2 cm 3 /J. After a characterization of the hybrid LC cell in terms of the recording laser power, we demonstrate holographic videos of red, green, and blue colors at a refresh rate of 25 Hz.